﻿A revision of the “spiny solanums” of Tropical Asia (Solanum, the Leptostemonum Clade, Solanaceae) - Xavier Aubriot; Sandra Knapp (PhytoKeys, 2022)
The Leptostemonum Clade, or the “spiny solanums”, is the most species-rich monophyletic clade of the large cosmopolitan genus Solanum (Solanaceae) and represents almost half the species diversity of the genus. Species diversity in the clade is highest in the Americas, but significant clusters of endemic taxa occur in the Eastern Hemisphere. We present here a taxonomic revision of the 51 species of spiny solanums occurring in tropical Asia (excluding the island of New Guinea, and the lowlands of Nepal and Bhutan). Three species are described as new: Solanum kachinense X.Aubriot & S.Knapp, sp. nov. from northern Myanmar, S. peikuoense S.S.Ying, sp. nov. from Taiwan, and S. sulawesi X.Aubriot & S.Knapp, sp. nov. from northern Sulawesi, Indonesia. Of the spiny solanums occurring in the region, 38 are native and 13 are introduced from the Americas or Africa, either as adventive weeds or as cultivated plants. Phylogenetic resolution amongst these taxa is still a work in progress, so we have chosen to treat these taxa in a geographical context to aid with identification and further taxon discovery. For the native species we provide complete nomenclatural details for all recognised species and their synonyms, complete descriptions, distributions including maps, common names and uses, and preliminary conservation assessments. For the introduced taxa that have been treated in detail elsewhere we provide details of types, synonyms based on tropical Asian material, general distributions, and common names for the region. We provide lecto- or neotypifications for 67 names; 63 for native and 4 for introduced taxa. All taxa are discussed and compared to similar species; keys are provided for all taxa. We illustrate all native species with herbarium and field photographs and introduced species with field photographs only. All specimens examined for this treatment are included in Suppl. materials 1–3 as searchable files.